Weak resonances of periodical nonlinear oscillations - Lavcel-Budko, Olga; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2017)
The mathematical model of nonlinear oscillations of weightless string is analyzed. Coefficients of the mathematical model and initial conditions are periodical functions of the space variable. A multiscale perturbation technique and integrating along characteristics are used to construct asymptotic solution without secular members.